Research experiences in the African Research Network on Agricultural by-Products (ARNAB) - Mosi, A.K.; Lambourne, L.J. (International Development Research Centre, 1983)
Briefly summarizes research results in utilizing crop residues as livestock feed in Africa; outlines the aims, envisaged specific activities & items that need to be given priority by the African Research Network on Agricultural By-products (ARNAB) and describes ILCA's current views & research approach on crop-residue use.